Efektivitas Model Pembelajaran Kooperatif Jenis Think Pair Share (TPS) terhadap Kemampuan Berpikir Kritis Siswa di Mata Pelajaran Pendidikan Pancasila Kelas 3 MI Darut Tauhid - Salsabila, Arini; Syamsudin, Syamsudin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This research is focused on assessing the efficacy of the cooperative learning approach known as Think Pair Share (TPS) in enhancing the critical thinking abilities of 3rd-grade learners at MI Darut Tauhid within the framework of Pancasila Education. This quantitative study utilized a one-group pretest-posttest design, involving a total of 24 students from class 3E selected through a census method. The evaluation tools employed included tests for critical thinking skills (both pretest and posttest) and observation sheets. Data analysis was conducted using the Wilcoxon Signed-Rank Test and the N-Gain test. The findings revealed a significant difference between the pretest and posttest results (p=0.004), confirming the effectiveness of the TPS model. Nevertheless, the N-Gain score of 0.217 categorized the effectiveness as low, suggesting that while some progress was made, the level of improvement was not yet optimal.